Review: Nanomaterials for Reactive Oxygen Species Detection and Monitoring in Biological Environments - Huynh, Gabriel T.; Kesarwani, Vidhishri; Walker, Julia A.; Frith, Jessica E.; Meagher, Laurence; Corrie, Simon R. (Frontiers in Chemistry, 2021)
Reactive oxygen species (ROS) and dissolved oxygen play key roles across many biological processes, and fluorescent stains and dyes are the primary tools used to quantify these species in vitro. However, spatio-temporal monitoring of ROS and dissolved oxygen in biological systems are challenging due to issues including poor photostability, lack of reversibility, and rapid off-site diffusion. In particular, ROS monitoring is hindered by the short lifetime of ROS molecules and their low abundance. The combination of nanomaterials and fluorescent detection has led to new opportunities for development of imaging probes, sensors, and theranostic products, because the scaffolds lead to improved optical properties, tuneable interactions with cells and media, and ratiometric sensing robust to environmental drift. In this review, we aim to critically assess and highlight recent development in nanosensors and nanomaterials used for the detection of oxygen and ROS in biological systems, and their future potential use as diagnosis tools.